Bat Ecotourism Potential At Wind Cave Nature Reserve, Sarawak Through Bat Conservation Study - Hasrulzaman Hassan, Basri; Mohammad Akmal-Syafriq, Rushisham; Qhairil Shyamri, Rosli; Muhd. Amsyari, Morni; Julius Willian, Dee; Faisal Ali, Anwarali Khan; Mohd Tajuddin, Abdullah; Mohd-Ridwan, Abdul Rahman (Faculty of Forestry, Universiti Putra Malaysia, 2017)
The study conducts roost site mapping, roost sites preferences, bat assemblage and bat acoustic call at the Wind Cave Nature Reserve (WCNR) from 2013 to 2015. The area lack information on bats and the existing information has not been updated for quite some time. The study utilizes the non-consumptive method that uses observation, data logger and the wildlife acoustic song meter to collect data. The data obtained are important as baseline data for future management and conservation of the bats species at the WCNR. This information also provides additional interesting information to tourists. This paper is a collection of the ecological studies of cave-dwelling bats that have been conducted at the WCNR. The findings from the study such as species list; and a map that show the location of the bats and their roost sites preferences can help increase awareness towards the conservation of bats at WCNR to promote better ecotourism benefit.